Upaya Peningkatan Volume Cairan Pada Pasien Dengan Demam Tifoid - Mutya, Eka; , Arina Maliya, S.Kep., Ns., M.Si.Med (2017)
Typhoid is a infection disease caused by distribution of salmonella on the gastrointestinal tract in small intestine characterizes by fever more than 7 days and disorder of gastrointestinal tract. The way of transmission un this disease is nearly occurs through contaminationed foo and drink. Salmonella thypi is gram negative bacterial, no capsule, have a flagella, and can not from spores. The thyfoid fever disease have a various complication, one of them is dehydration caused by nausea vomitting along fever so that cause probability of deficient fluid volume in patient with typhoid. The purpose from this research to increase the deficient fluid volume in patient with typhoid. So that's no complications cause by dehydration such as blood visocity and hipovolemic shock. The research conducted on February 〖20〗^th until February 〖25〗^th 2017. The methods used by the authors are observation interview and documentation. The results by the author is found a problem deficient fluid volume related to inadequate fluid intake secondary. Effect from nause vomitting. The intervention involve: asses a vital sign, asses a dehydration sign, asses a fluid balance, thrust intake per oral according with a body need, collaboration with doctor in giving fluid therapy. After implementation during 3x24 hours deficient fluid volume in resolved. The next plans to do in home are drink 8 glasses of water a day so it can be supply a fluid in body.